Description of a new Oriental stonefly species, Phanoperla constanspina (Plecoptera: Perlidae) from Mindanao, Philippines and association of life stages using DNA barcoding - Cruz, Ian Niel B. Dela; Nuñeza, Olga M.; Lin, Chung-Ping (Zootaxa, 2016)
A new perlid stonefly, Phanoperla constanspina sp. nov. is described from Mt. Malindang, northern Mindanao, Philippines. The male of the new species is distinguished by lacking lobes on penial sac and large black spines at the penial apex. The female is distinguished by the egg. DNA barcoding was used to associate male, female, and nymphal specimens with 0% divergence. Morphological variation was observed in the shape of the hemitergal anterior processes and the 9th tergal setal patches of male adult and body pigmentation of the nymph. A key to the Philippine Phanoperla species and a checklist of Oriental Phanoperla are also provided.